Productivity enhancement of Indian mustard (Brassica juncea) through innovative crop establishment technique - SINGH, HAR VIR; CHOUDHARY, R L; MEENA, M D; DOTANIYA, M L; MEENA, M K; JAT, R S; PREMI, O P; RAI, P K (The Indian Journal of Agricultural Sciences, 2019)
A field experiment was carried-out for two consecutive years 2016-17 and 2017-18 during winter at ICARDirectorate of Rapeseed and Mustard Research, Bharatpur, Rajasthan to evaluate the performance of Indian mustard (Brassica juncea L.) under innovative transplanting technique of crop establishment. The experiment was laid out in randomized block design with two factors, i) planting geometries, i.e. 30 × 30 cm (T1), 45 × 30 cm (T2) and 60 × 30 cm (T3) and ii) transplanting dates, i.e. 13th October (D1), 22nd October (D2) and 01st November (D3) with three replications. The maximum plant height (199.2 cm), leaf area index (5.82) and chlorophyll content (43.29) were recorded with T2 and D1 during both the years. The significantly higher value of yield attributes, i.e. length of siliquae, number of seeds/siliquae, test weight and oil content were also recorded with T2D1 treatment during both years. Seed yield was recorded maximum with T2D1 treatment during both the years. Seed yield improved significantly with T2 by 9.1 and 19.5% over T1 and T3 respectively, whereas, yield improvement with D1 also recorded significantly higher by 8.3 and 32.2% over D2 and D3, respectively. The maximum net returns (` 100835) and B:C ratio (3.77) was also found with T2 than the other treatments. Among the date of transplanting treatments, D1 recorded the maximum values of these monetary parameters. Thus, we can conclude that transplanting of mustard on 13th October with 45 × 30 cm planting geometry is beneficial for getting higher yield as well as net monetary returns in the Rajasthan.